2013
DOI: 10.1371/journal.pbio.1001712
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Molecular Comparisons of C. elegans and Mammalian Pharmacology Identify Distinct Targets That Regulate Feeding

Abstract: This paper takes advantage of similarities between the C. elegans and human pharmacopeia to identify and validate pharmacological targets that regulate C. elegans feeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…We therefore investigated the occurrence of colloidal aggregators among three recent whole organism phenotypic screens, two on zebra fish embryos 41,42 and one on worms. 43 Of 93 active, machine readable compounds identified in the three screens, nine would be predicted to aggregate. This is a rate far below that expected for compounds emerging from biochemical, target-oriented HTS campaigns, at least from primary screens, consistent with the idea that at least whole organism screens are much less likely to enrich colloidal aggregators than are target-based screens (we have not compared with cell-based phenotypic screens, where aggregators may well be more prevalent, though the direction of their effects is hard to predict).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore investigated the occurrence of colloidal aggregators among three recent whole organism phenotypic screens, two on zebra fish embryos 41,42 and one on worms. 43 Of 93 active, machine readable compounds identified in the three screens, nine would be predicted to aggregate. This is a rate far below that expected for compounds emerging from biochemical, target-oriented HTS campaigns, at least from primary screens, consistent with the idea that at least whole organism screens are much less likely to enrich colloidal aggregators than are target-based screens (we have not compared with cell-based phenotypic screens, where aggregators may well be more prevalent, though the direction of their effects is hard to predict).…”
Section: Resultsmentioning
confidence: 99%
“…We explored which combinations of conformer generation and E3FP parameters produced the most effective 3D fingerprints for the task of recovering correct ligand binders for over 2,000 protein targets using the Similarity Ensemble Approach (SEA). SEA compares sets of fingerprints against each other using Tanimoto coefficients (TC) and determines a p-value for the similarity among the two sets; it has been used to predict drug off-targets 4,5,37,38 , small molecule mechanisms of action [39][40][41] , and adverse drug reactions 4,42,43 . For the training library, we assembled a dataset of small molecule ligands that bind to at least one of the targets from the ChEMBL database with an IC 50 of 10 μM or better.…”
Section: Sea 3d Fingerprint Performance Exceeds That Of 2d In Bindingmentioning
confidence: 99%
“…This approach could enumerate testable hypotheses about how poorly understood and novel compounds affect behavioral phenotypes (Figure 3c). For example, in a recent study, we predicted targets for compounds found to modify C. elegans feeding behavior 61 . In the first stage, a screen yielded 84 phenotypically-related but structurally-diverse compounds, which we compared against more than two thousand human targets.…”
Section: Mining Phenotypically Related Compounds For Multi-target Mecmentioning
confidence: 99%